Pearl mussels (Margaritifera marocana) in Morocco: conservation status of the rarest bivalve in African fresh waters - Sousa, Ronaldo Gomes (2016)
Margaritifera marocana is one of the rarest freshwater mussel species (listed as critically endangered), and is endemic to Morocco. Despite its constrained distribution and low abundance, to date there are no quantitative studies addressing the conservation status of this species. Surveys were conducted in 36 sites along the Oum Er Rbia river basin (Rivers Derna, Laabid and Oum Er Rbia) to assess the distribution, abundance, population structure and genetic diversity of M. marocana. Just one specimen was found on River Oum Er Rbia and none on River Derna; however, a high abundance was found in the lower section of River Laabid (e.g., site Laabid 6 reached a mean density of 11.0 ± 6.8 ind.m(-2)). Contrary to earlier information, which reported an overall population size fewer than 250 individuals in a restricted area and no juvenile presence, this study showed that a much higher abundance exists in River Laabid alone. In addition, the species is present in more than 50 km of this river and is still recruiting since small specimens were found. Regarding genetic diversity, six of nine loci previously used in Margaritifera margaritifera were polymorphic and suitable in M. marocana. The spatial range contraction of this species is likely to be very recent, since no strong signature was detected by the molecular diversity indices. Information gathered in this study can be used as a reference to the present conservation status of M. marocana, and guide future research and management initiatives to better conserve it. We conclude discussing the potential major threats for the future survival of M. marocana and suggest some management measures (and research needs) that should be urgently applied.